Pengaruh Aromaterapi Lavender untuk Kualitas Tidur Pada Pasien Hemodialisa RS PKU Muhammadiyah Yogyakarta - Luthfiana Prisma Martuti; Ida Nurjayanti; Agus Rismanto (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Chronic Kidney Disease (CKD) is defined when kidney damage lasts more than 3 months. Chronic Kidney Disease (CKD) is a disease with various causes in the form of structural or functional abnormalities, accompanied by a decrease in glomerular filtration rate (GFR). People with chronic kidney disease and kidney failure often require kidney replacement therapy or hemodialysis. Sleep disorders are one of the complications of hemodialysis and often occur in patients with chronic kidney disease and over a long period of time. This can affect the quality of sleep of people with chronic kidney disease, both in terms of quantity and duration of sleep, which ultimately affects the individual's daily function. Non-pharmacological methods such as aromatherapy are important to relieve, prevent or treat certain diseases using natural plant spices or aromatic essential oils. Lavender aromatherapy belongs to the Lamiaceae family and its scientific name is Lavandula angustifolia. Inhaling lavender oil is a simple method that has been proven to have a positive effect on various symptoms, especially in hemodialysis patients with sleep disorders.